Cloning, nucleotide sequencing, and expression of tetanus toxin fragment C in Escherichia coli. - Fairweather, N F (1986)
The amino acid sequence of the first 30 residues of fragment C of tetanus toxin was determined, and a mixture of 32 complementary oligonucleotides, each 17 bases long, was synthesized. A 2-kilobase (kb) EcoI fragment of Clostridium tetani DNA was identified by Southern blotting and was cloned into the Escherichia coli plasmid vector pAT153 with the 32P-labeled oligonucleotide mixture as a probe. A second 3.2-kb Bg/II fragment was identified and cloned with the 2-kb EcoRI fragment as a probe. The nucleotide sequence of 1.8 kb of this DNA was determined and was shown to encode the entire fragment C and a portion of fragment B of tetanus toxin. The tetanus DNA was expressed in E. coli with pWRL507, a plasmid vector containing the trp promoter and a portion of the trpE gene. The trpE-tetanus fusion proteins were visualized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and were shown to react with anti-fragment C antibody.